Aplicación de láminas de agua para recuperación de suelo salino en maíz amarillo duro (Zea mays L.). Predio María Laura, Virú, La Libertad, 2019 - Tejada Soria, Anita Cecilia (2019)
In the present investigation is to evaluate the salinity conditions of the property María Laura located in Los Cerritos, Virú valley, with aims of recovering 100% of the soil, which has been affected by salinity, to give a better production of the crop and improve the quality of the soil. The best alternative of solution that allows to establish in an economical, practical and simple way to recover the soil is through the application of irrigation water, since the water is economical in this area of the Virú valley, and since its water table is below of 2.50 meters does not need another recovery alternative such. Previously, laboratory analyzes were carried out with the purpose of detecting the level of salinity found in the terrain, these tests were carried out taking into account the indicated parameters. With the results obtained from soil samples (pH, texture, C.E., S.A.R., E.S.P., anions and cations) and water (pH and C.E.), it was possible to determine what volume of water should be applied to the land, this type of research saw feasible since the land was in time of rest to change of crop. The correction irrigation water that is applied is the sum of the irrigation water plus the washing sheet; since first the soil must be saturated to later wash this, and thus a desired result can be achieved. The most efficient irrigation water for this terrain and crop is 54 cm, since we must take into account the salinity tolerance of the dent corn crop